Refurbishment and Conversion to Pumped/Storage Systems of Hydroelectric Power Plants in C????ba (Argentina) (London Journal of Engineering Research, 2025)
This research presents a comprehensive methodology for the technical and environmental assessment of the refurbishment and modernization of existing hydroelectric plants in the province of Crdoba (Argentina) to use pumped storage hydropower (PSH) systems. The study is based on leveraging existing civil infrastructure, with the goal of minimizing environmental impacts, optimizing economic resources, and improving provincial energy management.The proposed methodology combines technical, hydrological, environmental, and water resource management criteria to prioritize sites with high conversion feasibility. Of the total number of plants analyzed, four were identified as having favorable conditions: Fitz Simon, Cassaffousth, Los Molinos I, and La Via. Field campaigns and specific analyses were subsequently conducted to assess the technical and operational feasibility of their refurbishment and modernization. The results show that the selected plants have high potential to operate with pumped storage energy storage schemes, contributing to the integration of intermittent renewable energy and strengthening the provincial electricity grid.The case of the La Via Power Plant is presented in detail, given its current modernization process, highlighting the technical and economic opportunity of incorporating the reversible pumping function simultaneously with the equipment upgrade.
Keywords: Carbon nanotubes (CNTs); Functionalization of CNTs; Chirality; Arc discharge; laser ablation; Biosensors.; manufacturing.; industry; Technological tasks; metalworking; visualization of the axiom control CNC system; energy storage; hydroelectric power; pumped storage; hydropower station modernisation; infrastructure refurbishment.